The Janthinobacterium sp. HH01 genome encodes a homologue of the V. cholerae CqsA and L. pneumophila LqsA autoinducer synthases. - Claudia Hornung (Public Library of Science (PLoS), 2013)
Janthinobacteria commonly form biofilms on eukaryotic hosts and are known to synthesize antibacterial and antifungal compounds. Janthinobacterium sp. HH01 was recently isolated from an aquatic environment and its genome sequence was established. The genome consists of a single chromosome and reveals a size of 7.10 Mb, being the largest janthinobacterial genome so far known. Approximately 80% of the 5,980 coding sequences (CDSs) present in the HH01 genome could be assigned putative functions. The genome encodes a wealth of secretory functions and several large clusters for polyketide biosynthesis. HH01 also encodes a remarkable number of proteins involved in resistance to drugs or heavy metals. Interestingly, the genome of HH01 apparently lacks the N-acylhomoserine lactone (AHL)-dependent signaling system and the AI-2-dependent quorum sensing regulatory circuit. Instead it encodes a homologue of the Legionella- and Vibrio-like autoinducer (lqsA/cqsA) synthase gene which we designated jqsA. The jqsA gene is linked to a cognate sensor kinase (jqsS) which is flanked by the response regulator jqsR. Here we show that a jqsA deletion has strong impact on the violacein biosynthesis in Janthinobacterium sp. HH01 and that a jqsA deletion mutant can be functionally complemented with the V. cholerae cqsA and the L. pneumophila lqsA genes.